Disease Modifying Therapies in Multiple Sclerosis: A Review - Raza, Mohsin (Nepal Journal of Neuroscience, 2023)
Multiple Sclerosis is a autoimmune demyelinating disease of the nervous system.This review paper evaluates disease modifying therapies for multiple sclerosis , a chronic autoimmune disease of the central nervous system. Over 20 Disease Modifying Therapies are available, categorized into injectables, oral agents, and infusions. The review covers their efficacy, safety, and tolerability. Established injectable Disease Modifying Therapies include interferon beta and glatiramer acetate, while newer oral agents like fingolimod offer conveniencewith more adverse effects. Infusions like natalizumab have higher efficacy but greater risks of adverse events. The paper also discusses newer Disease Modifying Therapies like cladribine. Treatment should be individualized based on patient characteristics, risk factors, and treatment goals. Overall, this review provides a comprehensive summary to aid clinicians in selecting appropriate Disease Modifying Therapies for Multiple Sclerosis.